2002
DOI: 10.1080/13556210120091473
|View full text |Cite
|
Sign up to set email alerts
|

Neurological aspects of areca and betel chewing

Abstract: Betel quid chewing has been claimed to produce a sense of well-being, euphoria, warm sensation of the body, sweating, salivation, palpitation, heightened alertness and increased capacity to work. These effects suggest that betel quid chewing affects predominantly the central and autonomic nervous systems. Several studies have been conducted to elucidate the central and autonomic effects of betel quid chewing. The results are: (1) betel quid chewing increased the heart rate with onset within 2 minutes, maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
98
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 16 publications
2
98
0
Order By: Relevance
“…Betel chewers claim that betel chewing produces facial flushing and a warm sensation in the body. Dizziness, hot sensations, palpitations and sweating are associated with betel nut consumption in habitual users (Chu 2002;Deng et al 2001;Norton 1998). These findings might shed light on the interesting association between chewing betel nut and an increased likelihood of experiencing hot flashes, although careful inspection and systematic study is required on this topic.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Betel chewers claim that betel chewing produces facial flushing and a warm sensation in the body. Dizziness, hot sensations, palpitations and sweating are associated with betel nut consumption in habitual users (Chu 2002;Deng et al 2001;Norton 1998). These findings might shed light on the interesting association between chewing betel nut and an increased likelihood of experiencing hot flashes, although careful inspection and systematic study is required on this topic.…”
Section: Discussionmentioning
confidence: 84%
“…The nut is consumed in its raw and ripe form, in a processed form (boiled and dried/ sundried), or in a fermented form (soaked in water for a few days when it is ripe). Recent studies on humans have shown that the predominant effects of betel quid chewing appear to be exerted on the central and autonomic nervous systems, and these effects are habit related and dose dependent (Chu 2002;Deng et al 2001). Betel chewing produces an increase in heart rate, blood pressure, sweating and body temperature (Wyatt et al 1996;Chu 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Arecoline, the main alkaloid present at up to 1% of dry weight, is thought to be responsible for a central cholinergic stimulation and monoamine transmission, which then activates both sympathetic and parasympathetic effects (6,7). Arecoline has been further shown to be implicated in the pathogenesis of oral diseases because of its genotoxic, mutagenic, and carcinogenic potential (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…Arecoline, the major alkaloid present out of nine alkaloids found in the betel nut, possesses potent muscarinic action (Chu, 2001) and has now found an application in Alzheimer's disease (Sullivan et al, 2000). The biological effects of betel quid chewing related to health hazards have been reviewed (Chu, 2002;Gupta & Ray, 2004;Jeng et al, 2001;Trivedy et al, 2002;Warnakulasuriya et al, 2002;Winstock, 2002). These include neuronal dependence and oral health hazard leading to development of oral squamous cell carcinoma, including the preceding leukoplakia and submucous fibrosis.…”
Section: Introductionmentioning
confidence: 99%